2017
DOI: 10.3171/2017.1.peds16541
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological consideration of medullary streaks on FLAIR imaging in pediatric moyamoya disease

Abstract: OBJECTIVEMedullary streaks detected on fluid-attenuated inversion recovery (FLAIR) imaging have been considered to be reflected ischemic regions in pediatric moyamoya disease. The purpose of this study was to evaluate these medullary streaks both clinically and radiologically and to discuss associated pathophysiological concerns.METHODSThe authors retrospectively reviewed data from 14 consecutive pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…However, this is not true in pediatric cases with moyamoya disease, which can exhibit linear hyperintensities that extend into the perivascular space of the deep white matter in FLAIR imaging [ 39 ]. These linear hyperintensities, which have been called medullary streaks, are thought to be associated with vasculature [ 40 ] or might result in a stagnation of cerebrospinal fluid of the perivascular spaces [ 41 ]. Because of this difference in adult and pediatric patients with moyamoya disease, pediatric patients were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not true in pediatric cases with moyamoya disease, which can exhibit linear hyperintensities that extend into the perivascular space of the deep white matter in FLAIR imaging [ 39 ]. These linear hyperintensities, which have been called medullary streaks, are thought to be associated with vasculature [ 40 ] or might result in a stagnation of cerebrospinal fluid of the perivascular spaces [ 41 ]. Because of this difference in adult and pediatric patients with moyamoya disease, pediatric patients were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Revascularization surgery for improving a patient's hemodynamics can prevent the development of strokes, but is known to be associated with perioperative cerebral infarction and cerebral hyperperfusion causing transient neurological deterioration, delayed intracerebral hemorrhage, and vasogenic edema. [1], [2], [3], [4], [5], [6], [7] In this case, radiologic examination revealed no ischemic lesion on POD 1, but within 3 days, abnormal intensity changes were noted throughout the cortical and subcortical regions.…”
Section: Discussionmentioning
confidence: 58%
“…The utility of the T2 FLAIR sequence for the assessment of MMD has been extensively investigated. 21,22,28,43,48,63 The "ivy sign," an indicator of slow or retrograde flow in cortical vessels, can help characterize the origins of collateral supply, correlates with cerebrovascular reactivity (CVR), and can improve in response to revascularization surgery, or it can temporarily worsen after revascularization in the setting of hyperperfusion. 21,28,48 In the cerebral white matter, linear T2 hyperintense streaks perpendicular to the lateral ventricle, referred to as "medullary streaks," have been described.…”
mentioning
confidence: 99%
“…21,28,48 In the cerebral white matter, linear T2 hyperintense streaks perpendicular to the lateral ventricle, referred to as "medullary streaks," have been described. 63 The pathophysiology of medullary streaks is incompletely understood, but is thought to be associated with ischemia and these may represent collateral vasculature, increased CSF, and edema. 63 Additionally, Komatsu et al reported that T2 FLAIR can demonstrate areas of parenchymal white matter T2 hyperintensity that variably reverse after revascularization.…”
mentioning
confidence: 99%
See 1 more Smart Citation